Integrated Nutrient Management on Soybean in a Coastal Charland of Bangladesh (Bangladesh Agronomy Journal, 2017)
A field experiment was conducted at Char Jangalia under MLT site, Laxmipur, a coastal district of southern Bangladesh, during Rabi season of 2015-16 to evaluate the effect of integrated nutrient management on growth and yield performance of soybean (var. Glycine max L.). Six treatment combinations, viz. T1= Control, T2= Farmers practice (25-15 Kg NP ha-1, T3= 100% recommended dose (30-25-55 Kg NP ha-1, K), T4= 50 % recommended dose + 1.5 t ha-1 vermi compost, T5= 50 % recommended dose + 5 t ha-1compost and T6=50 % recommended dose + 1.2 kg ha-1 bio fertilizer were tested. The experiment was laid out in randomized complete block design with 3 replications. There were significant differences among the different treatment combinations in terms of yield and yield contributing characters. Integrated nutrient management with application of 50% of the recommended doses of urea, TSP, MoP, and biofertilizer (Bradyrhizobium) at the rate of 1.2 kg ha-1 significantly increased most of the parameters, such as the plant height, number of nodule per plant, pods per plant, seeds per pod and seed yield. The highest seed yield (2.93 t ha-1) was recorded from T6 while the lowest seed yield (1.83 t ha-1) was obtained from T1. The highest gross return (Tk.117200 ha-1) and gross margin (Tk. 71840 ha-1) was obtained from T6, whereas the lowest gross return (Tk. 70400 ha-1) and gross margin (Tk.27880 ha-1) was obtained from T1. The overall results indicated that the application of integrated nutrient management of a combination of bio fertilizer with 50% N-P-K (15- 12.5-27.5 Kg ha-1) of the recommended dose produced the maximum nodulation and seed yield of soybean in the southern coastal char land.Bangladesh Agron. J. 2017, 20(1): 77-83